The Effect of Basic Life Support Short Film on Knowledge of Cardiac Arrest First Aid: Original Article: Original Article - Fatmawati, Nilam; Hidayati, Nur; Maghfuroh, Lilis (Jurnal Surya, 2025)
Introduction: Cardiac arrest is a life-threatening emergency that frequently occurs outside hospital settings. Mortality rates increase due to lack of knowledge in administering first aid for cardiac arrest. One approach to enhancing public knowledge of basic life support is through education. To determine the impact of basic life support education using a short film on knowledge levels regarding first aid for cardiac arrest. Methods: This study employed a pre-experimental one-group pre-test post-test design. The research was conducted on March 15, 2025, involving 31 members of Nasyiatul Aisyiyah in Padenganploso Village, Pucuk, Lamongan, selected through total sampling. Knowledge levels were assessed using a questionnaire on basic life support and analysed using the Wilcoxon test (α≤ 0.05). Results: All respondents were female, with 58.1% aged 31–40 years. Before the intervention, 65.5% of respondents had low knowledge levels; this improved to 87.1% of respondents having good knowledge levels after the intervention. Statistical analysis confirmed a significant effect of short film-based education on knowledge of basic life support (p=0.000). Conclusion: Short films can be used as a means to increase knowledge of basic life support, as they engage both visual and auditory senses, facilitating better understanding and memory retention. Future studies should consider including a control group and a larger sample size to strengthen the findings.